Kualitas pengelolaan keuangan: keterampilan dan pengetahuan pegawai dalam mengoperasikan SISMIOP pada Badan Pengelola Keuangan dan Pendapatan Daerah Kabupaten Tasikmalaya - Wardhani, Dyah Ciptaning Lokiteswara Setya; Rusliana, Nanang (Universitas Widya Mataram, 2023)
This study aims to determine the effect of skills and knowledge of human resources on the implementation of quality of financial management at BPKPD, Tasikmalaya Regency. This type of research is explanatory research that explains the causal relationship between variables through hypothesis testing. This study used a sample of 25 respondents. Sampling using a saturated sample technique. The test equipment used is a research instrument test and multiple regression analysis. From the results of this test, it can be concluded that the significance value (Sig) of the skill that there is an influence between skill and the quality of financial management, the significance value (Sig) of the knowledge variable means that there is an influence between skills and quality of financial management and the value of R Square is 0.848 which implies that the skills and knowledge variables affect the quality of financial management 84.80% while the rest is influenced by other variables outside this regression equation or variables that are not examined.